Kerajinan Tikar Purun di Kelompok Masyarakat Pimpinan Daerah Aisyiyah Kuala Pembuang Seruyan - Nurul Hikmah Kartini; Yuni Rahayu; Anita Rahman; Siti Marjanah; Dina Noor Laila Ramadhani; Ifan Supiyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Purun mats as a pearl of local wisdom in Central Kalimantan must continue to be developed. The lack of people who produce purun mats as an essential part of carrying out the training of purun weaving mats needs to be held. The group of mothers who usually deliver their children/grandchildren who go to school is the focus of this community service activity. The Universitas Muhammadiyah Palangkaraya through the Institute for Research and Community Service (LP2M) and students carrying out the Community Service Program (KKN) gave an important role in increasing the knowledge and manufacture of purun matting products. This activity aims to provide skills, improve knowledge and produce woven mats of purun in the target community groups. From community service activities, it is recommended that it be carried out sustainably in the same community groups in the location with various forms of training. This is done so that more skills are mastered and bring benefits both economically and non-economically.